CHARACTER DEVELOPMENT THROUGH ISLAMIC SCHOOL CULTURE IN SMP DAAR EN NISA ISLAMIC SCHOOL - Yuniar, Kiki; Soesanto, Soesanto; Made Sudana, I (Educational Management, 2020)
Character education is important in the development of student character. This qualitative research aims to analyze the implementation of character education through school culture layers and character values developed through school culture in the SMP Daar en Nisa Islamic School. Data were collected through interviews, observation and document study methods with Miles and Huberman's interactive data analysis models. The researcher tested the credibility of the data through triangulation of sources and methods. The results showed that school culture-based character education was carried out through 1) routine activities which included worship worship activities, learning the Al Quran, Muslimah Study, Speak It Up, Clean School Movement (CSM), and internalization of manners and order; 2) spontaneous activities carried out through direct reprimands from teachers to students and between students; 3) teacher's example in the form of exemplary in carrying out worship, discipline and attitude and speech; and 4) school conditioning includes environmental conditioning and students. The values of character education instilled through school culture are 1) religious values with faith and submission to God Almighty, tolerance and caring the environment as its sub values; 2) independent values with discipline, hard work, responsibility as its sub values; 3) mutual cooperation with cooperation and solidarity as its sub value; and 4) integrity value with honest and polite as its sub values.